1986
DOI: 10.7326/0003-4819-105-3-356
|View full text |Cite
|
Sign up to set email alerts
|

Nonresponsiveness to Hepatitis B Vaccine in Health Care Workers

Abstract: Twenty-eight health care workers who had a poor antibody response when initially vaccinated with hepatitis B vaccine were revaccinated with three additional 20-microgram doses. Eight of the twenty nonresponders, who had levels of antibody to hepatitis B surface antigen (anti-HBs) of less than 8 estimated radioimmunoassay (RIA) units, and all 8 of the hyporesponders, who had anti-HBs levels of 8 or 16 RIA units, attained anti-HBs levels of 36 RIA units or more after revaccination. Tests for HLA-A, B, C, and DR;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
4
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(107 citation statements)
references
References 25 publications
9
93
4
1
Order By: Relevance
“…Usually, one would expect patients with autoimmune diseases to be high responders instead of low responders. Our results differ from Craven et al [5], Cooksley et al [4], and Walker et at. [27] with regard to DR-7, which they found elevated.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Usually, one would expect patients with autoimmune diseases to be high responders instead of low responders. Our results differ from Craven et al [5], Cooksley et al [4], and Walker et at. [27] with regard to DR-7, which they found elevated.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, A-10, B-12, CW-5, DR-3, and DR-5 were found to be increased in histocompatibility testing, whereas DR-2 was decreased. With regard to DR-3, this is in agreement with Craven et al [5]. Paradoxically, an increased frequency of HLA-DR-3 was also seen in patients with autoimmune chronic active hepatitis [15].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Individuals responding to vaccination with the induction of a high anti-HBsAg titer showed a strong T cell response non-responsiveness (HBsAg titer < 10 kU/L) to vaccination are associated with certain human leukocyte antigen (HLA)-class Ⅱ alleles. DRB1*0301, DRB1*0701, and DQB1*0201 [5,8,9] were shown to have a higher prevalence in non-responders, whereas other antigens (DRB1*0101, *1301, *1501, and DPB1*0401) seem to mediate strong immune responses [9][10][11][12] . Higher age, obesity, male gender, smoking, and chronic dialysis are risk factors for a non-/ low-responsiveness [8,9,[13][14][15] .…”
Section: Resultsmentioning
confidence: 99%
“…Hepatitis B vaccinations prevent HBV infections as well as its complications in most of the vaccines [3,4] . However, 5% to 10% fail to produce protective anti-HBsAg titers after three vaccinations irrespective of the source of the antigen, which is a problem not only for health care workers, and represents a major medical as well as economic challenge [5][6][7] . Low-(HBsAg titer 10-99 kU/L) or Abstract AIM: To evaluate, whether humoral hepatitis-B-vaccine non-responders also fail to mount a T cell response and to compare these results to normal vaccines.…”
mentioning
confidence: 99%